(untitled) (Universal International Scientific Journal, 2026)
This article discusses the relationship between nature and society, man and the environment in which he lives, and valeology. The article discusses the development of methods and techniques for forming a healthy lifestyle, the opinions of specialists in this regard, and our invaluable values ​​in promoting a healthy lifestyle in holy books. The views of great scholars and thinkers on the importance of a healthy lifestyle in the upbringing of young people, the role of the science of valeology in educational institutions in increasing the effectiveness of ideological and educational and propaganda work are analyzed.